(untitled) - Ngindi, Buhle

The stability of productivity and fruit quality traits of ‘Fuji’ apples on different Rootstocks (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScAgric)--Stellenbosch University, 2024.